A Single Noninterleaved Metasurface for High‐Capacity and Flexible Mode Multiplexing of Higher‐Order Poincaré Sphere Beams. Issue 6 (26th December 2019) - Jiang, Zhi Hao; Kang, Lei; Yue, Taiwei; Xu, He‐Xiu; Yang, Yuanjie; Jin, Zhongwei; Yu, Changyuan; Hong, Wei; Werner, Douglas H.; Qiu, Cheng‐Wei
Abstract: Cylindrical vector vortex beams, a particular class of higher‐order Poincaré sphere beams, are generalized forms of waves carrying orbital angular momentum with inhomogeneous states‐of‐polarization on their wavefronts. Conventional methods as well as the more recently proposed segmented/interleaved shared‐aperture metasurfaces for vortex beam generation are either severely limited by bulky optical setups or by restricted channel capacity with low efficiency and mode number. Here, a noninterleaved vortex multiplexing approach is proposed, which utilizes superimposed scattered waves with opposite spin states emanating from all meta‐atoms in a coherent manner, counter‐intuitively enabling ultrahigh‐capacity, high‐efficiency, and flexible generation of massive vortex beams with structured state‐of‐polarization. A series of exemplary prototypes, implemented by sub‐wavelength‐thick metasurfaces, are demonstrated experimentally, achieving kaleidoscopic vector vortex beams. This methodology holds great promise for structured wavefront shaping, vortex generation, and high information‐capacity planar photonics, which may have a profound impact on transformative technological advances in fields including spin‐Hall photonics, optical holography, compressive imaging, electromagnetic communication, and so on. Abstract : A noninterleaved vortex multiplexing approach is proposed, which utilizes superimposed scattered waves with opposite spin states emanating from all meta‐atoms on a shared‐aperture metasurface in a coherent manner. This counter‐intuitively enables ultrahigh‐capacity, high‐efficiency, and flexible generation of massive higher‐order Poincaré sphere beams. This methodology may have a profound impact on advances for wavefront sculpturing, electromagnetic communication, planar photonics, etc.